The Influence of Entrepreneurial Management on MSMEs Performance through Competitive Advantage in Sidoarjo Regency - Faustina, Thalita Al; Muzdalifah, Laily; Novie, Muhafidhah; Sholikhah, Afifatus (Institute of Computer Science (IOCS), 2025)
The purpose of this study is to contribute to the field of strategic management by examining the influence of entrepreneurial management on the performance of MSMEs, mediated by competitive advantage. Entrepreneurial management involves creative efforts and a willingness to take calculated risks to support the success of programs that improve business competitiveness. Although this topic is highly relevant, research integrating entrepreneurial management and competitive advantage as mediating variables in the context of MSME performance remains limited. This gap may hinder understanding of how entrepreneurial strategies affect business outcomes and the mechanisms involved. In this study, 89 MSME actors in Sidoarjo were selected as respondents using the Cluster Sampling technique to ensure broad regional representation. Cluster sampling is a method of taking samples by dividing the population into several groups or clusters. Data were collected through structured questionnaires and analyzed using SmartPLS 4 statistical software for robust results. Findings reveal that entrepreneurial management has a significant positive impact on MSME performance and strengthens competitive advantage. However, competitive advantage does not directly influence performance, making entrepreneurial management the primary driver of MSMEs success in competitive environments. These results highlight the importance of strengthening managerial capabilities through innovation, strategic planning, and responsive decision-making. The study provides a foundation for government and institutions to design targeted training and mentoring programs. It also enriches the strategic management literature on MSMEs and offers empirical insights relevant to policy formulation and the development of empowerment initiatives, particularly in Sidoarjo Regency